Candida auris: Problems in Diagnostics and Management - Artem A. Ivanov; Tatiana V. Kulichenko (Вопросы современной педиатрии)
Fungal infections in these days have the major risk for patients who receive immunosuppressive therapy and suffer from immunodeficiency conditions during their long stay in a hospital. The literature review is dedicated to Candida auris that was firstly isolated in 2009. Later it was reported that this fungus is the cause of nosocomial infections which mortality rate reaches 72%. C. auris has multi-drug resistance and it can survive for a long time in the environment. The lack of sensitivity of diagnostic tests for this fungus detection is the main problem in clinical practice. This leads to inappropriate management and increases the risk of mortality due to infection. C. auris was included in the group of infectious agents that has the highest danger to public health according to the recent report of the Centre for Disease Control (USA).